ANALYSIS OF SOFTWARE PRODUCTS USED FOR AUTOMATION OF ACCOUNTING BY ENTREPRENEURSHIP SUBJECTS - Ponomareva, Tetiana; Matiushko, Mariia (Social Economics, 2021)
Nowadays, information technology plays an important role in accounting. They cover various aspects of accounting and are endowed with significant advantages over manual methods. In modern conditions of formation of digital economy in Ukraine the value of efficiency of introduction of information technologies and automation of accounting and financial accounting by subjects of business activity has reached a high level. If for large enterprises it is not difficult to buy ready-made software solutions, then for small businesses and private enterprises it is quite difficult to choose the independent formation of the accounting information system. We find the fact that for all entrepreneurs equally important issues are the choice of configuration and model of construction of the accounting information system, taking into account the peculiarities of doing business, reporting and the level of application of accounting automation.In this scientific article we analyze the software products that are directly used to automate accounting, and their capabilities for this type of accounting. We identify the main advantages and disadvantages of this transition from paper to electronic document storage, as well as the difficulties of accounting in Ukraine, opportunities, tasks and the transition to automated accounting. We consider software products used for automated accounting and financial reporting, namely: "Microsoft Excel", "1C: Enterprise", "Sail", "MASTER: Accounting". We construct a comparative description of the software by studying the advantages and disadvantages of installing and using these products for accounting and reporting in small, medium and large organizations. We evaluate the technical requirements and the necessary software features of various domestic software products to decide on the most effective way to organize automated accounting.